On the method of surgery and applications : surgery - Agama, Theophilus (My University, 2022)
In this paper we introduce the concept of surgery. This concept ensures that almost all discontinuous functions can be made to be continuous without redefining their support. In spite of this, it preserves the properties of the original function. Consequently we are able to get a handle on the number of points of discontinuities on a finite interval by having an information on the norm of the repaired function and vice-versa.
Keywords: surgery; discontinuity; support